2001
DOI: 10.1161/01.atv.21.4.509
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Light Chain Kinase Regulates Capacitative Ca 2+ Entry in Human Monocytes/Macrophages

Abstract: Abstract-Monocytes/macrophages are present in all stages of atherosclerosis. Although many of their activities depend to various extents on changes in intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ), mechanisms regulating [Ca 2ϩ ] i in these cells remain unclear. We aimed to explore the role of myosin light chain kinase (MLCK) in Ca 2ϩ signaling in freshly isolated human monocytes/macrophages. Large capacitative Ca 2ϩ entry (CCE) was observed under fura 2 fluoroscopy in human monocytes/macrophages treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…One agent that gave particularly encouraging results was ML-9 [1-(5-chloronaphthalene-1-sulfonyl)homopiperazine, HCl], a drug known to inhibit myosin-light-chain kinase (MLCK) (Saitoh et al, 1986;Saitoh et al, 1987). Previous reports demonstrated inhibition of SOCE by ML-9, and this was taken as evidence for a role of myosin light chain kinase in this signaling pathway (Watanabe et al, 1996;Norwood et al, 2000;Tran et al, 2001). We analyzed SOCE in HEK293 cells using a standard Ca 2+ add-back assay, whereby intracellular Ca 2+ stores were depleted by treating cells with thapsigargin in the presence of nominal extracellular Ca 2+ , followed by restoration of extracellular Ca 2+ to 1.8 mM.…”
Section: Ml-9 Inhibits Soce and I Cracmentioning
confidence: 96%
See 1 more Smart Citation
“…One agent that gave particularly encouraging results was ML-9 [1-(5-chloronaphthalene-1-sulfonyl)homopiperazine, HCl], a drug known to inhibit myosin-light-chain kinase (MLCK) (Saitoh et al, 1986;Saitoh et al, 1987). Previous reports demonstrated inhibition of SOCE by ML-9, and this was taken as evidence for a role of myosin light chain kinase in this signaling pathway (Watanabe et al, 1996;Norwood et al, 2000;Tran et al, 2001). We analyzed SOCE in HEK293 cells using a standard Ca 2+ add-back assay, whereby intracellular Ca 2+ stores were depleted by treating cells with thapsigargin in the presence of nominal extracellular Ca 2+ , followed by restoration of extracellular Ca 2+ to 1.8 mM.…”
Section: Ml-9 Inhibits Soce and I Cracmentioning
confidence: 96%
“…Previous studies that have demonstrated inhibition of SOCE by ML-9 have generally attributed this effect to inhibition of MLCK, the characterized target of ML-9 (Watanabe et al, 1996;Takahashi et al, 1997;Norwood et al, 2000). However, this conclusion has only been corroborated with molecular data in one study, in which an antisense oligonucleotide targeted to the gene encoding MLCK inhibited SOCE in human monocytes/macrophages (Tran et al, 2001). In our hands, significant knockdown of MLCK protein expression by siRNA did not have any measurable effect on store-depletion-induced rearrangement of EYFP-Stim1.…”
Section: Reversal Of Stim1 Localization By Ml-9mentioning
confidence: 98%
“…To further examine the interaction between STIM1 and the Ca 2ϩ regulated AC, a pharmacological tool was used to disrupt translocation of endogenous STIM1 to the plasma membrane in response to store depletion. ML-9, a piperazine-based MLCK inhibitor has previously been shown to inhibit CCE (Watanabe et al, 1996;Norwood et al, 2000;Tran et al, 2001). The effects of ML9 on CCE suggested a role for MLCK in store-mediated Ca 2ϩ entry.…”
Section: Ml-9 An Inhibitor Of Stim1 Puncta Formation and Cce Prevenmentioning
confidence: 97%
“…Although the activation mechanisms and entry pathways of store-operated Ca 2+ entry are not fully clarified, Orai1 and TRPC family are candidates for Ca 2+ entry pathway (28 -30) and STIM1 is considered as a Ca 2+ sensor located on the intracellular Ca 2+ stores (31). Furthermore, it has been reported that cytoskeletons and their regulators, including actin (32), cofilin (33), tubulin (34), and myosin light chain kinase (35), are involved in the cellular mechanisms of storeoperated Ca 2+ entry. According to proteome analysis of control and TGF β 1 -treated A549 cells, various proteins involved in cytoskeletal modulations were up-regulated in A549 cells undergoing EMT (7).…”
Section: Discussionmentioning
confidence: 99%